Investigation on the Effect of Origin of Carbon Steel Reinforcing Bar on the Corrosion Behavior in Artificial Concrete Solution - Abdulkareem M.A. Al-Sammarraie (Journal of Global Pharma Technology, 2016)
The corrosion of steel reinforcing bar in concrete is very important point in fractures and damage of concrete building structures, many factors play important role in this problem. This research focuses on the effect of the origin of the carbon steel reinforcing bar on the corrosion parameters in simulate concrete solution (artificial), consisted of (Ca (OH) 2 (2gm), KOH (22.44mg), Noah (8mg). Two familiar types in the Iraqi local markets were followed, namely; locally produced sample and Ukrainian imported samples. Tafel plots and cyclic polarization procedures were conducted to estimate the corrosion parameters and pitting susceptibly of the two types using three electrodes potentiostat.The effect of temperature and some thermodynamic functions were measured in the range 20 to 50ᴼC. The microstructure and morphology was imaged using optical and atomic force microscope (AFM) respectively.Keywords: Steel reinforcing, Concrete solution, Artificial, Tafel.